Jurnal ILMU KOMUNIKASI: THE CHINESE MEDIA FRAMING OF THE 2015’S TIANJIN EXPLOSION - Li Yan, Lin Lidong (PRODI IKOM UAJY, 2017)
This study compares the framing’s patterns of the Chinese traditional media and social media in reporting the incident of Tianjin explosion in 2015. Applying frame-building and framesetting theory, this study explores the interplay between online opinions available on Weibo and the Chinese newspapers in different phases of the crisis event. Moreover, it examines the differences in framing the incident between the state-owned party media and the commercial media